Systolic blood pressure variability and lower extremity amputation in a non-elderly population with diabetes. (April 2016) - Budiman-Mak, Elly; Epstein, Noam; Brennan, Meghan; Stuck, Rodney; Guihan, Marylou; Huo, Zhiping; Emanuele, Nicholas; Sohn, Min-Woong
Highlights: Excessive systolic blood pressure variability was a significant and strong predictor of major amputations in the lower extremities. Significant graded relationship between SBP variability and major amputation was found in both normotensive and hypertensive groups. Persons with existing peripheral vascular disease may not be subject to this graded relationship. Abstract: Objective: Systolic blood pressure (SBP) variability is emerging as a new risk factor for cardiovascular diseases, diabetic nephropathy, and other atherosclerotic conditions. Our objective is to examine whether it has any prognostic value for lower-extremity amputations. Research design and methods: This is a nested case-control study of a cohort of patients with diabetes aged < 60 years and treated in the US Department of Veterans Healthcare system in 2003. They were followed over five years for any above-ankle (major) amputations. For each case with a major amputation (event), we randomly selected up to five matched controls based on age, sex, race/ethnicity, and calendar time. SBP variability was computed using three or more blood pressure measures taken during the one-year period before the event. Patients were classified into quartiles according to their SBP variability. Results: The study sample included 1038 cases and 2932 controls. Compared to Quartile 1 (lowest variability), Quartile 2 had 1.4 times (OR = 1.44, 95% CI = 1.00–2.07) and Quartiles 3 and 4 (highest) had 2.5 times (OR for Quartile 3 = 2.62, 95% CI = 1.85–3.72; OR for Quartile 4 = 2.50, 95% CI = 1.74–3.59) higher risk of major amputation ( P for trend < 0.001). This gradient relationship held in both normotensive and hypertensive groups as well as for individuals without prior peripheral vascular disease. Conclusions: This is the first study to show a significant graded relationship between SBP variability and risk of major amputation among non-elderly persons with diabetes.